Polymerization of heterocycles (ring opening) : main lectures presented at the International Symposium on Polymerization of Heterocycles (Ring-Opening), Warsaw-Jabonna, Poland, 23-25 June, 1975 - Penczek, S. (Stanisaw) (Pergamon Press, 1977)
Polymerization of Heterocycles (Ring Opening) is a collection of papers presented at the International Symposium on Polymerization of Heterocycles (Ring-Opening) held in Warsaw, Poland on June 23-25, 1975. The first paper describes the developments and physical meaning of ion pairs and higher ionic aggregates. Another paper explains the process of obtaining linear polymers, containing rings in the main chain. The book interprets the various behaviors of polymers that can result in high optical yields of stereoelectivity ratios equal to 8. The text then discusses future trends in aldehyde and.